Enhancing ESL Vocabulary Acquisition through AI-Based Learning Systems - Tanvir Mostafa (PT. Academic Bright Collaboration, 2026)
Purpose – Vocabulary is one of the key aspects of second-language development, as it facilitates reading, listening, speaking, and writing. Nevertheless, because lexical development needs to be practiced repeatedly, with long-term motivation and long-term memory encouragement, many ESL learners have problems with remembering and applying new vocabulary. Recent advancements in artificial intelligence (AI) have provided new opportunities for vocabulary teaching in the form of adaptive practice, automated feedback, multimodal support, simulated dialogue, and long-term progress monitoring.Methods – This narrative review explores how AI-based learning systems can be used to support vocabulary acquisition in ESL learners based on existing research on vocabulary learning, technology-assisted language learning, and recent research on AI and generative tools.Findings – According to the literature reviewed, AI-assisted learning may be helpful if systems deliver tasks of suitable difficulty, the ability to repeat and retrieve information, contextualized input and feedback. Nonetheless, the success of AI relies on good pedagogy, prudent design of instructions, validation of results and teacher mediation.Research implications – Critical issues include misinformation, privacy issues, and learners’ overreliance on technology.Originality – AI should be seen as an auxiliary resource and not a substitute for principled vocabulary instruction.